The Biopharmaceutical Properties of Solid Dosage Forms: I. An Evaluation of 23 Brands of Phenylbutazone Tablets - Searl, R. O. (1967)
The potency, disintegration and dissolution characteristics of 23 brands of phenylbutazone tablets were determined. Five (21.7%) of the 23 brands failed to comply with the minimum requirements of the compendia or the regulations appended to the Food and Drugs Act. The in vitro characteristics of four brands were substantially different from those that disintegrated and released the drug satisfactorily. The in vivo characteristics of three of the four brands were compared with those observed for a pharmaceutically acceptable product. The latter product released the drug to the blood quickly, but the former products released the drug only after the tablets had been in the body for six to eight hours and, in the case of one product, released quantities much below those that would be acceptable to the physician. These results show that different products containing the same drug are not necessarily equivalent. This is contrary to the generic equivalency hypothesis which assumes that all products comply with specifications and, therefore, must be clinically effective.